2019
DOI: 10.1111/ijn.12776
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine gluconate transparent dressing does not decrease central line‐associated bloodstream infection in critically ill patients: A randomized controlled trial

Abstract: Background: Central line-associated blood stream infections are accompanied by increased mortality and health care costs. The application of different types of dressings in infection control has not been fully investigated to date. Aim:To assess the effects of two different dressing types on central line-associated bloodstream infections. Methods:A randomized, nonblinded, controlled trial was conducted. Central lines were randomly allocated to intervention (chlorhexidine gluconate transparent dressing, n = 259… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
(30 reference statements)
0
11
0
1
Order By: Relevance
“…The selected studies included 18 RCTs 19-36 and 2 quasi-experimental studies, 37,38 and all of them were performed in hospital settings. Furthermore, 6 studies were multicentric (≥ 2 hospitals), [19][20][21][22][23]27 14 studies were performed on adults, [20][21][22][23][24][25][27][28][29]31,[33][34][35]38 and 6 studies examined neonates or pediatric populations. 19,26,30,32,36,37 Of the studies with this information, 13 included ICU patients, 19,[21][22][23][24][25][26]29,32,[34][35][36][37] 4 included onco-hematological patients, 27,30,31,33 and 1 included non-ICU patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The selected studies included 18 RCTs 19-36 and 2 quasi-experimental studies, 37,38 and all of them were performed in hospital settings. Furthermore, 6 studies were multicentric (≥ 2 hospitals), [19][20][21][22][23]27 14 studies were performed on adults, [20][21][22][23][24][25][27][28][29]31,[33][34][35]38 and 6 studies examined neonates or pediatric populations. 19,26,30,32,36,37 Of the studies with this information, 13 included ICU patients, 19,[21][22][23][24][25][26]29,32,[34][35][36][37] 4 included onco-hematological patients, 27,30,31,33 and 1 included non-ICU patients.…”
Section: Resultsmentioning
confidence: 99%
“…28 The definition of CRBSI, exit-site and tunnel infections, and adverse events varied across the studies (Appendix 4 online). Also, 5 studies reported CRBSI rates ≥ 2.0 per 1,000 catheter days 21,25,27,30,35 in at least one study group and 2 studies reported CRBSI rates <1.5 per 1,000 catheter days in both groups. 22,23…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vor jeglichen Manipulationen an einem ZVK sowie mit ihm verbundenen Dreiwegehähnen muss eine hygienische Händedesinfektion sowie eine Desinfektion des Dreiwegehahns durchgeführt werden [7] [20]. In anderen gab es keine signifikante Reduktion der katheterassoziierten Blutstrominfektionen [21]. In weiteren Studien konnte eine Reduktion auch mit Verbänden ohne aseptischen Wirkstoff mit nachhaltigem Effekt erzielt werden.…”
Section: Manipulationen An Devicesunclassified